25 years of Austria's EU membership: Quantifying the economic benefits with a DSGE model - Fritz Breuss (Austrian Institute of Economic Research (WIFO), 2020)
Austria's EU accession 25 years ago, alongside Finland and Sweden, was preceded by an extended period of convergence toward the EU: via the free trade agreement concluded with the EC in 1973, and the participation in the European Economic Area (EEA) in 1994. Although the COVID-19 crisis in 2020 seems to overshadow the overall positive balance of 25 years of EU membership, on average the real GDP growth dividend amounted to 0.8 percentage points per year since 1995. To check the robustness of this result, obtained with an integration macro model, a DSGE model for Austria is used here. Usually other methods are applied to estimate integration effects: trade gravity models, CGE models, macro models. Following in't Veld's (2019) approach with a DSGE model for the EU, we adapt an earlier version of the two-country DSGE model for Austria and the Euro area (Breuss and Rabitsch, 2009) to evaluate the benefits of Austria's EU membership. It turns out that grosso modo the macro results can be confirmed with the DSGE model.
Keywords: F15; C51; O52; 330; European Integration; Model simulations; country studies